2018
DOI: 10.1111/jopr.12796
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Oral Health‐Related Quality of Life, Peri‐Implant and Kinesiograph Parameters in Wearers of One‐or Two‐Implant Mandibular Overdentures

Abstract: This study suggested that 1-IOD can improve patient OHRQoL and may be similar to 2-IODs in preservation of both peri-implant parameters and masticatory movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
1
28
4
1
Order By: Relevance
“…The greater retention provided by the SIO is probably responsible for our increased opening and closing velocities. This finding is in accordance with a recent kinesiograph study that showed improved on vertical opening of elderly participants rehabilitated with SIO prostheses after 3 months of use (25).…”
Section: Discussionsupporting
confidence: 93%
“…The greater retention provided by the SIO is probably responsible for our increased opening and closing velocities. This finding is in accordance with a recent kinesiograph study that showed improved on vertical opening of elderly participants rehabilitated with SIO prostheses after 3 months of use (25).…”
Section: Discussionsupporting
confidence: 93%
“…In the past decades, two-implant retained overdenture is considered as the first choice for treatment for patients with edentulous mandibles that were poorly adapted to conventional dentures (1,2). However, many patients refused this treatment modality due to their fear from surgical procedures (3)(4)(5). Moreover, this treatment remains inaccessible for patients with poor socio-economic conditions, and higher surgical risks due to impaired health conditions (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence-based studies (7)(8)(9)(10) and randomized controlled trials (RCTs) (3,4,11,12) showed that retaining the existing mandibular denture by a single midline implant might be considered as a potential alternative treatment for completely edentulous patients. Cordioli et al used delayed loading protocol and ball attachment with 100% implant survival rate after 5 years (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations